2017
DOI: 10.1039/c7ra00274b
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and stability enhancement of inverted perovskite solar cells via the addition of metal nanoparticles in the hole transport layer

Abstract: Inverted perovskite solar cells with enhanced efficiency and stability are fabricated based on a nanoparticles doped hole transport layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 31 publications
(29 reference statements)
0
30
0
1
Order By: Relevance
“…In organic optoelectronic devices such as OPVs and OLEDs, the photostability can be greatly enhanced by introducing metal nanoparticles (NPs) into the active layer . Sygletou et al reported that active materials mixed with surfactant‐free Al NPs can enhance the stability of BHJ OPV devices .…”
Section: Approaches To Overcome the Instability Caused By Degradationmentioning
confidence: 99%
“…In organic optoelectronic devices such as OPVs and OLEDs, the photostability can be greatly enhanced by introducing metal nanoparticles (NPs) into the active layer . Sygletou et al reported that active materials mixed with surfactant‐free Al NPs can enhance the stability of BHJ OPV devices .…”
Section: Approaches To Overcome the Instability Caused By Degradationmentioning
confidence: 99%
“…Due to the manufacturing procedure of the inverted PSC, the embedding of solution-processed metallic nanoparticles at different layers of the device other than the perovskite, e.g. inside the PEDOT:PSS and the PCBM carrier transporting layers, is possible without increasing the cost [16] as well as maintaining the planar architecture [29]. This way, plasmonic enhancement could be exploited without reducing the perovskite material, albeit at the price of reduced local field enhancement in the absorbing perovskite layer.…”
Section: Plasmonic Nanoparticles Inside Different Than the Perovskitementioning
confidence: 99%
“…Employing this approach allows employment of thinner perovskite layers, and thus reduction of the structure toxicity, without scarifying the PSC performance. Placing nanoparticles in PEDOT:PSS is considered a reliable strategy regarding the enhancement of the overall efficiency of the solar cell since studies have been shown it to favor the electrical properties of the system too [16], [29].…”
Section: Plasmonic Nanoparticles Inside Different Than the Perovskitementioning
confidence: 99%
“…The highest PCE reported thus far for the perovskite solar cells is 22.1%, and the cost of perovskite solar cell can be lower than that of the traditional energy sources . In terms of device fabrication, highly crystalline perovskite thin films can be prepared via solution process, such as printing or coating procedure, which are considered as simple and economical mass production procedures. High vacuum‐based thermal evaporation is typically used to deposit the metal electrode for the perovskite solar cells, which tends to be the bottom neck for the mass production of perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%